2019
DOI: 10.1016/j.iref.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of economic policy uncertainties in predicting stock returns and their volatility for Hong Kong, Malaysia and South Korea

Abstract: Highlights• We analyze the predictability of stock return and its volatility of Hong Kong, Malaysia and South Korea • We base on the measure of domestic and global economic policy uncertainties (EPU) • Linear Granger causality tests fail to find evidence of predictability from EPU • A nonparametric causality-in-quantiles test, however, finds strong evidence of causality • Nonparametric test is found to be more robust relative to the standard linear causality test. AbstractThis paper analyzes whether we can pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 45 publications
1
37
0
1
Order By: Relevance
“…Furthermore, investigating EPU in developed markets i.e. US also conclude its dynamic impact on international equity market returns with respect to portfolio diversification (Mensi et al, 2014;Balcilar et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, investigating EPU in developed markets i.e. US also conclude its dynamic impact on international equity market returns with respect to portfolio diversification (Mensi et al, 2014;Balcilar et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Closely related to risk prevention of extreme risk, tail risk, spillover etc., accurate volatility prediction can provide valuable information for market investors, policy makers, economic activities ( Bollerslev, Hood, Huss, & Pedersen, 2018 ; Ma, Liao, Zhang, & Cao, 2019 ). Although it is difficult to improve forecasting accuracy, increasing studies document that popular uncertainty indexes, EPU and VIX, contain useful information for forecasting stock market volatility ( Balcilar, Gupta, Kim, & Kyei, 2019 ; Bekaert & Hoerova, 2014 ; Brogaard & Detzel, 2015 ; Liu & Zhang, 2015 ). Specifically, Liang, Wei, and Zhang (2020) investigate the VIX's forecasting ability for eight international stock markets, the results indicate VIX index exhibits powerful predictive ability.…”
Section: Introductionmentioning
confidence: 99%
“…The literature exploring the connection of return and/or volatility of the stock market with EPU has flourished across the globe, including both developed and emerging economies. Extensive research has mainly concentrated on exploring the relationship of own country EPU with the returns/volatility of local stock markets (Bekiros et al, 2016;Rahman et al, 2019) among others, while various studies explored the transnational influences of EPU on the stock markets of other emerging economies such as Brazil, Australia, Canada, Japan, China, South Africa, and on the financial markets of some trade group countries such as ASEAN, BRIC, EU and GCC (Balcilar et al, 2019;Carri ere-Swallow & C espedes, 2013;Istiak & Alam, 2019;Kang & Ratti, 2015) among others.…”
Section: Relevant Researchmentioning
confidence: 99%
“…The authors used a counterfactual approach of nonparametric kernel density estimation technique and concluded that Chinese EPU explains variations in prices of AH shares, and significantly decreases AH premium share index returns. Furthermore, some studies have also explored the spillover effects of Chinese EPU on macro-economic activities (see, for example, Fontaine et al, 2017;Yan, 2018), leverage decisions of shipping firms in Thailand (Kotcharin & Maneenop, 2018) stock markets (Balcilar et al, 2019;Tsai, 2017).…”
Section: Relevant Researchmentioning
confidence: 99%